Non-take-up as a social experience. Towards a typology of not claiming social benefits - Barbara Lucas (Culture, Practice & Europeanization)
Non-take-up of financial social benefits is a prominent issue for contemporary welfare states, and studies exploring its causes have proliferated recently. However, most analyses are based on an “incapacity framework” or refer to a “rational choice model”, which makes it difficult to access the meaning that people attach to non-take-up. Based on qualitative research on the non‑take‑up of financial benefits by families living in Geneva, Switzerland, this paper proposes to explore this meaning by considering non-take-up as a social experience situated at the intersection of different logics of action: integration, strategy and subjectivation. This approach enables us to grasp how social inequalities, stigmatisation and discrimination – as structural explanations for non-take-up theorised separately in the literature – together help to shape different meanings of non-take-up. More precisely, we identify four meanings of not claiming social benefits in the narratives of the people interviewed, which are captured through four figures: Non-take-up as a means to combat social exclusion (Mr. Breadwinner); non-take-up as a consequence of the inadequacy of social policies (the Single Mother); non-take-up as part of an intergenerational integration project (the Migrant Worker); and non-take-up as an ethical stance (the Ethical Intellectual).